Glacier loss and hydro-social risks in the Peruvian Andes - Mark, Bryan G.; French, Adam; Baraer, Michel; Carey, Mark; Bury, Jeffrey; Young, Kenneth R.; Polk, Molly H.; Wigmore, Oliver; Lagos, Pablo; Crumley, Ryan; McKenzie, Jeffrey M.; Lautz, Laura (Global and planetary change, 2017)
Accelerating glacier recession in tropical highlands and in the Peruvian Andes specifically is a manifestation of global climate change that is influencing the hydrologic cycle and impacting water resources across a range of socio-environmental systems. Despite predictions regarding the negative effects of long-term glacier decline on water availability, many uncertainties remain regarding the timing and variability of hydrologic changes and their impacts. To improve context-specific understandings of the effects of climate change and glacial melt on water resources in the tropical Andes, this article synthesizes results from long-term transdisciplinary research with new findings from two glacierized Peruvian watersheds to develop and apply a multi-level conceptual framework focused on the coupled biophysical and social determinants of water access and hydro-social risks in these settings. The framework identifies several interacting variables—hydrologic transformation, land cover change, perceptions of water availability, water use and infrastructure in local and regional economies, and water rights and governance—to broadly assess how glacier change is embedded with social risks and vulnerability across diverse water uses and sectors. The primary focus is on the Santa River watershed draining the Cordillera Blanca to the Pacific. Additional analysis of hydrologic change and water access in the geographically distinct Shullcas River watershed draining the Huaytapallana massif towards the city of Huancayo further illuminates the heterogeneous character of hydrologic risk and vulnerability in the Andes. •Glacierized hydro-social systems in the Andes are being transformed by global change.•Risks to water access in these systems are heterogeneous, dynamic, and interlinked.•Coupled biophysical and social dimensions mediate and amplify these risks.•A transdisciplinary approach elucidates interactions and feedbacks across dimensions.•A conceptual framework for analyzing these risk dynamics across scales is presented.